Management of Extracurricular Activities at SD Hj. Isriati Baiturrahman 1 Semarang (Educational Management, 2022)
The study aims to analyze achievements of SD Hj. Isriati Baiturrahman 1 Semarang is classified as a large number, so researchers need to know more about the extracurricular management used by the school. It is believed that good management, including extracurricular management, needs to pay attention to four things. The four things in question include planning, organizing, implementing, and evaluating. This research is a qualitative research with a case study approach. Sources of data were taken from document studies, interviews, and observations regarding extracurricular management at SD Hj. Isriati Baiturrahman 1 Semarang. The data validation technique used is the data source triangulation technique. The data analysis technique used in this study is the Miles, Huberman and Saldana model, which consists of data reduction, data presentation, and drawing conclusions. Based on the research findings and discussion, it was found that the four components had been carried out well by the school. The conclusion of this study is the extracurricular management used by SD Hj. Isriati Baiturrahman 1 Semarang has been running well, so it is only natural that the school has many non-academic achievements.